Corporate Criininal Responsibility and the Public Welfare Offence - Skenderis, James (My University, 2001)
This thesis will provide an analysis of corporate criminal responsibility by examining the evolving nature of the public welfare offence in Canada and how it affects I the traditional understanding of mens rea. Historically, criminal law has been founded upon the notion of individual responsibility. Criminal convictions were restricted to human beings as only they could possess the mental and physical elements required of crimes. Since corporations are not considered living persons, the law has dealt with corporate offenders primarily through the establishment of public welfare offences. These offences are mainly I policy-oriented and do not require proving a mental element. However, there is noW a growing concern due to the influence of the Canadian Charter of Rights and Freedoms that public welfare offences should be regarded in the same manner as true crimes and offenders given similar legal protections. This view is troublesome as it raisFs questions over whether corporations can be equated with moral persons and given the same rights and privileges. If such a perspective is adopted, the enforcement of public welfare offences could be jeopardised resulting in increased infractions that might undermine the original policy-oriented objectives that public welfare offences were based upon. This thesis attempts to find a solution to this predicament by examining the viability of a modified corporate personality view where corporations could be 'treated' like persons, but not regarded as full-fledged moral entities; thus, allowiqg them some but not all the legal protections that human beings possess. Furthermore, the feasibility of such a position is examined in accordance with a normative view of the: criminal law, which allows for the inclusion of both individuals and collectives as responsible agents by not restricting the definition of mens rea to a purely mentalist interpretation.
Keywords: Philosophy; Philosophy